The unbearable dispersal of being: narrativity and personal identity in borderline personality disorder - Schmidt-Boddy, Philipp; Fuchs, Thomas (Phenomenology and the cognitive sciences, 2021)
Borderline personality disorder (BPD) is characterized by severe disturbances in a subject’s sense of identity. Persons with BPD suffer from recurrent feelings of emptiness, a lack of self-feeling, and painful incoherence, especially regarding their own desires, how they see and feel about others, their life goals, or the roles to which they commit themselves. Over the past decade or so, clinical psychologists, psychotherapists, and psychiatrists have turned to philosophical conceptions of selfhood to better understand the borderline-specific ruptures in the sense of identity, which are frequently associated with severe affective instability and turbulence in interpersonal relationships. Fuchs (2007) has suggested that these disturbances in self-experience can best be described and explained by using notions—widely discussed in philosophy and psychology—of narrativity and narrative identity. On such a narrative view, key features of BPD present significant modifications of proto-narrative structures and inhibit the development of a narrative identity, resulting in a disturbed sense of identity. Although the role of narrativity in BPD has been acknowledged by many researchers, some have voiced dissatisfaction with what they take to be limitations of a narrativistic understanding of the disorders of identity characterizing BPD, and have proposed alternative, allegedly non-narrativistic, accounts. In this paper, we critically examine an example of the latter, viz. Gold and Kyratsous’ (2017) account of the person as an intrapersonal team reasoner. We defend a narrativistic understanding of BPD identity disorder against their objections. To this end, we propose a broader, and more finely-differentiated, concept of narrativity. On this account, four aspects of narrativity are distinguished, the disordering of which can affect those with BPD. As it turns out, our account implies that even Gold and Kyratsous—in order to ground their approach—must either make use of these aspects or propose an as-yet unarticulated alternative. This casts doubt upon whether their approach is non-narrativistic after all.
Published online: 15 December 2020
Gesehen am 29.01.2024